PENGARUH PEMBERIAN REWARD DAN PUNISHMENT YANG DIPERKUAT DENGAN AYAT-AYAT AL QUR’AN TERHADAP MOTIVASI BELAJAR SISWA - Cucun Kholifah; Toto Santi Aji (Jurnal PGSD, 2022)
The purpose of research at SDN 2 tukmudal is to analyze the application of reward and punishment methods whether to affect the student's study of class V at SDN 2 tukmudal. the type of research used is quantitative survey research. The data retrieval method used in this study was a questionnaire (questionnaire) with a Likert scale instrument. While the sample technique used in this study is non-probability, which means sampling techniques that do not give equal opportunity or opportunity for each element or member of the population to be selected as a sample. The researcher took a sample at SDN 2 Tukmudal which amounted to 47 students. Based on the results of the study, it could be concluded that there was a significant impact by administering reward and punishment for the study of students at the lower level of 23.5% tukmudal and 76, 5% was affected by other factors. This is also reinforced by the verses of the Qur'an. Keyword : Reward, Punishment dan Motivasi Belajar